El cocoliche en cuestión (El Hilo de la Fabula, 2019)
Cocoliche is a variety arising from the contact between Spanish and Italian in historical and geographic conditions —in particular, the two great waves of 1880–1914 and 1945–1955 and the region of the Argentine Coast, respectively. Although reduced by selection and simplification processes, it was nourished by the different Italian dialects. The change of the immigrant’s language had social importance: the result of the contact among different languages and dialects affected many of the most striking characteristics of the so–called «River Plate linguistic peculiarity».
Keywords: Contact; dialect; pluriformism; italianism